PELATIHAN PENGUATAN KOMITMEN PEGAWAI DALAM RANGKA PENYUSUNAN PROGRAM KERJA BERDASARKAN VISI DAN MISI LEMBAGA - Hakim, Lukman; Aminuddin Aziz, Abdullah; Suwandi, Suwandi; Budiarti, Erika Mei; Niswah MZ, Isniyatun (ABIDUMASY, 2025)
In relation to employee performance, organizational culture has an influence on employee work commitment, namely in terms of support, similarity of values ​​and norms in the workplace, and internal employee motivation. Employee commitment is one of the most important dimensions in an organization that can be used as an indicator of assessing the tendency of employees whether they are still able to survive or not in the institution/organization. Surviving here is also directed at achieving the vision and mission of the institution. Employee commitment to survive and fight in an institution is also determined by the clarity of the vision and mission that is formed, the similarity of perception of the existing vision and mission, and the existence of clear direction from the leadership of the institution in order to condition all work programs and employee commitments towards achieving the vision and mission.